Data Protection in the EU and its Implications on Software Development outside the EU - Kneuper, Ralf (Journal of Institute of Science and Technology, 2019)
In May 2018, the General Data Protection Regulation (GDPR 2016) came into effect in the European Union (EU), defining requirements on how to handle personal data of EU citizens. This report discusses the effects of this regulation on software development organisations outside the EU, and summaries the software requirements that result from GDPR and therefore apply to most information technology (IT) systems that will handle data of individuals based in the EU.